ANALYSIS OF THE INFLUENCE OF SIZE, LEVERAGE, TOBINS’ Q AND CASH FLOW ON CORPORATE CASH HOLDINGS - Hakim Ali (Conference In Business, Accounting, And Management (CBAM), 2015)
Holding liquid assets such as cash can be a double-edged sword for a firm. On the one hand,  it  provides  flexibility  to  firms  allowing  them  to  avoid  costs  from  underinvestment  in positive-NPV projects due to lack of resources. Cash holding is an important asset on firms' balance sheets, receives much attention from companies, investors, and analysts. The objectives of this research are to analyse the impact of size, leverage, Tobins’Q and cash flow to cash holdings. The research methods used are descriptive research and explanatory research. Sampling in this study using purposive sampling, which is the manufacturer companies that listed at IDX in period 2010-2012. The technique analyses used are multiple regressions with classic assumption. The  classic  assumption  consists  of  normality testing,  multicollinearity,  heteroscedasticity  and autocorrelation. Based on the result and analysis, the conclusion that can be drawn in this research are: (1) There is positive impact of size to cash holdings, (2) There is impact of leverage to cash holdings, (3) There is impact of Tobin’s Q to cash holdings, (4) There is impact of cash flow to cash holdings.  Keywords: size, leverage, Tobin’s Q, cash flow, cash holdings.